Efeito da solarização e incorporação de repolho na supressão da murcha bacteriana em tomateiro - Moraes, Myrna Furtado Hilal (2006)
The most important plants disease of the world is the bacterial wilt. Integrated development is the best form of disease control because, had its complexity. The objective of the present research was to evaluate the effect solarization and of the incorporation the cool cabbage, wilt bacterial suppression in tomatoes plants. The assays had been carried through in the Microbiology Laboratory and the National Institute of Space Research - INPE, UEMA-MA. The isolated chosen teams had been gotten of samples collected at different times and local, having the necessity of if carrying through an aggressiveness verification. After choice the pathogenic isolated, was made the evaluation of the dosages and times of cabbage incorporation in the ground for bacterial wilt suppression, being this experiment implanted in greenhouse. This experiment is followed completed randomized experimental, with the following treatments: five times of incorporation and five dosages of cool cabbage, with four repetitions. Solarization evaluation of the ground was installed in field, where parcels had been prepared and artificially inoculated with Ralstonia solanacearum. These had been irrigated and re-covered with transparent plastic with 100 μm of thickness and left displayed to the sun for distinct periods. The solarization experiment was blocktype randomized with four periods of solarization (15, 30, 45 and 60 days), one witness inoculated and non-solarized, with six repetitions each treatment. With relation to the solarization and incorporation of cabbage tests, the parcels had been also prepared as in the previous experiment. The experiment block-type was randomized with biocontrol three forms (cabbage, solarization and cabbage+solarization), one witness inoculated, non-solarized and not-incorporated with six repetitions each treatment. The incorporated cabbage to the ground presented a low index of bacterial wilt to the 0 days of incorporation in the dosage of 20 g/L, and to the 60 days of incorporation in 100 g/L, respectively. It didn’t have difference significant statistics among the incorporated vegetal residues, except the 15 days in the cabbage dosage of 20 g/L, that can a high index of bacterial wilt observe. Among the periods of sun exposition, it has been seen that in the periods of 15 and 45 days it had significant difference statistics with relation to the other treatments how much to the number of dead plants. The solarization associated to the cabbage incorporation revealed potentially efficient the bacterial wilt suppression.